Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian di e-commerce Shopee di Kalangan Gen Z di Wilayah Kecamatan Bangil - Mawarda, Nur Ayu; Nurhidayah, Nurhidayah; Amin, Muh Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study explores the impact of technology and the internet on shopping behaviors, particularly through platforms like Shopee. The increasing popularity of online transactions has led to changes in consumer habits, with more people preferring online shopping over traditional stores. The research focuses on whether factors such as product quality, price, and promotion influence purchasing decisions on the Shopee application in Bangil sub-district. Using an explanatory research design with a quantitative approach, the study collected data through online questionnaires distributed via angket to 105 Shopee application users in Bangil District. The findings reveal that price, product quality, and promotion collectively have a significant positive effect on purchasing decisions. However, product quality alone does not impact purchasing decisions, while both price and promotion individually influence the decisions of Shopee application users in Bangil District Keywords: Product Quality, Price, Promotion, Purchasing Decisions